Effect of thermal annealing on sensing properties of optical fiber sensors coated with indium tin oxide nano-overlays - Michalak, Bartosz; Sezemský, Petr; Stranak, Vitezslav; Smietana, Mateusz (Photonics Letters of Poland, 2020)
In this work we discuss an effect of thermal annealing on optical and electrical properties of indium tin oxide (ITO) thin films deposited on a short section of multimode polymer-clad silica (PCS) optical fiber core. ITO films were deposited using different configuration of high power impulse magnetron sputtering (HiPIMS) and radio frequency magnetron sputtering (RF MS) cathodes. Due to tuned ITO film thickness it was possible to observe for these structures a lossy-mode resonance (LMR) and trace changes in properties of the films. Electrical resistance of the ITO overlays was also measured. Both optical and electrical measurements were repeated after annealing at 200°C in a tube furnace and nitrogen atmosphere. The measurements have shown that thermal annealing changes optical response to external refractive index (RI) of the fiber sensor and also changes the ITO layer resistivity. As an effect of thermal annealing we observed a shift of the LMR towards longer wavelengths. In addition as a result of annealing, the resistivity of the ITO layer was reduced. Full Text: PDF References M. Sobaszek et al., "Optical monitoring of thin film electro-polymerization on surface of ITO-coated lossy-mode resonance sensor", Proc. SPIE, vol. 10323, pp. 103234W, 2017. CrossRef I. Del Villar et al., " Generation of lossy mode resonances by deposition of high-refractive-index coatings on uncladded multimode optical fibers", J. Opt., vol. 12, no. 9, pp. 95503, 2010. CrossRef M. Śmietana et al., "Simultaneous optical and electrochemical label-free biosensing with ITO-coated lossy-mode resonance sensor", Biosensors and Bioelectronics, vol. 154, pp. 112050, 2020. CrossRef P. Niedziałkowski et al., " Electrochemical performance of indium-tin-oxide-coated lossy-mode resonance optical fiber sensor", Sensors and Actuators B: Chemical, vol. 301, no. 12, pp. 1-10, 2019. CrossRef V. Stranak et al., "Effect of mid-frequency discharge assistance on dual-high power impulse magnetron sputtering", Surface & Coatings Technology, vol. 206, no. 11-12. pp. 2801-2809, 2012. CrossRef I. Del Villar et al., "Design rules for lossy mode resonance based sensors", Appl. Opt., vol. 51, no. 19, pp. 4298-4307, 2012. CrossRef W. F. Wu and B. S. Chiou, "Effect of annealing on electrical and optical properties of RF magnetron sputtered indium tin oxide films", Appl. Surf. Sci., vol. 68, no. 4, pp. 497-504, 1993. CrossRef M. Smietana et al., "Optical Monitoring of Electrochemical Processes With ITO-Based Lossy-Mode Resonance Optical Fiber Sensor Applied as an Electrode", J. Light. Technol., vol. 36, no. 4, pp. 954-960, 2018. CrossRef M. Śmietana et al., "Study on Combined Optical and Electrochemical Analysis Using Indium‐tin‐oxide‐coated Optical Fiber Sensor", Electroanalysis, vol. 31, no.2, pp. 398-404, 2019. CrossRef